Tren dan Tantangan Transformasi Digital pada UMKM: Systematic Literatur Review - Masitoh, Gustina; Yadi, Yadi; Rohmah, Miftakhur; Carolina, Debi; Azmiyati, Afifah (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
Digital transformation has become a crucial requirement for Micro, Small, and Medium Enterprises (MSMEs) to enhance their competitiveness in the technological era. This study aims to examine the trends and challenges faced by MSMEs in the digitalization process through a systematic literature review (SLR) approach. A total of 35 scholarly articles published within the last five years were analyzed using specific inclusion and exclusion criteria. The findings indicate that the digitalization trends among MSMEs encompass the adoption of cloud-based technologies, the use of social media for marketing, the utilization of e-commerce platforms, and the integration of digital financial systems. However, the main challenges identified include low digital literacy, limited infrastructure, relatively high implementation costs, resistance to change, and insufficient policy support. This study not only provides a comprehensive understanding of the current state of MSME digital transformation but also identifies research gaps that have been rarely discussed. Furthermore, it offers strategic directions for researchers, MSME practitioners, and policymakers to develop more targeted strategies in accelerating and expanding digital transformation within Indonesia’s MSME sector.